The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0896-6273(00)80988-5
|View full text |Cite
|
Sign up to set email alerts
|

neurogenin1 Is Essential for the Determination of Neuronal Precursors for Proximal Cranial Sensory Ganglia

Abstract: The NEUROGENINS (NGNs) are neural-specific basic helix-loop-helix (bHLH) transcription factors. Mouse embryos lacking ngn1 fail to generate the proximal subset of cranial sensory neurons. ngn1 is required for the activation of a cascade of downstream bHLH factors, including NeuroD, MATH3, and NSCL1. ngn1 is expressed by placodal ectodermal cells and acts prior to neuroblast delamination. Moreover, NGN1 positively regulates the Delta homolog DLL1 and can be negatively regulated by Notch signaling. Thus, ngn1 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
682
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 692 publications
(709 citation statements)
references
References 83 publications
23
682
1
2
Order By: Relevance
“…Ngn-1 is essential for the specification of trigeminal sensory neurons (Ma et al, 1998). The present RT-PCR experiments demonstrate that ngn-1 expression at the trigeminal ganglion axial level is positively regulated by Shh signaling.…”
Section: Participation Of Shh Signaling In the Specification Of Trigesupporting
confidence: 51%
See 2 more Smart Citations
“…Ngn-1 is essential for the specification of trigeminal sensory neurons (Ma et al, 1998). The present RT-PCR experiments demonstrate that ngn-1 expression at the trigeminal ganglion axial level is positively regulated by Shh signaling.…”
Section: Participation Of Shh Signaling In the Specification Of Trigesupporting
confidence: 51%
“…It has been reported that ngn-2 is a specification factor for distal placode-derived sensory neurons in epibranchial ganglia (Fode et al, 1998). In the same ganglia, ngn-1 is essential for the specification of proximal neural crest-derived sensory neurons (Ma et al, 1998). Thus, ngn-1 and ngn-2 function in different regions in epibranchial ganglia.…”
Section: Effects Of Signaling Molecules On the Expression Of Neurogeninsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, members of the basic helixloop-helix transcription factor family, neurogenin1 (ngn1) and neurogenin2 (ngn2) are expressed in different subsets of ganglia dependent on species, and functional analyses showed that ngn genes are important for the development of the epibranchial ganglia (Fode et al, 1998;Ma et al, 1998;Schlosser and Northcutt, 2000;AbuElmagd et al, 2001;Andermann et al, 2002). Indeed, ectopic expression of ngn1 induces formation of excessive neurons in Xenopus and zebrafish embryos (Ma et al, 1996;Blader et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors neurogenin, foxd3 and NeuroD (Fode et al, 1998;Ma et al, 1998;Kim et al, 2001;Andermann et al, 2002), chemokine guidance receptor Cxcr4b (Knaut et al, 2005;Haas and Gilmour, 2006), and cell adhesion molecule cadherin-2 (Kerstetter et al, 2004) have been implicated in the development of the cranial ganglia and/or lateral line system.…”
Section: Introductionmentioning
confidence: 99%